Voice for the voiceless : over seven decades of struggle with China for my land and my people - Bstan-ʼdzin-rgya-mtsho, Dalai Lama XIV, 1935- (William Morrow, an imprint of HarperCollinsPublishers, 2025)
"In this unique book offering personal, spiritual, and historical reflections--some never shared before--His Holiness the Dalai Lama tells the full story of his struggle with China to save Tibet and its people for nearly seventy-five years"--